No angels: women who commit violence - Myers, Alice; Wight, Sarah M.A (Pandora, an imprint of HarperCollins Publishers, 1996)
Introduction / Sarah Wight and Alice Myers -- The guilt of the innocent and the innocence of the guilty: the cases of Marie Fahmy and Ruth Ellis / Anette Ballinger -- Partners in crime: defending the female of the species / Sean French -- Trying the Brookside two: domestic violence, soap opera, and real life / Tracy Hargreaves -- Retelling the tale: the Emma Humphreys case / Elizabeth Stanko and Anne Scully -- Fighting for freedom: suffragette violence against their state / Emily Hamer -- All too familiar: gender, violence, and national politics in the fall of Winnie Mandela / Rachel Holmes -- Phallocentric slicing: 20/20's reporting of Lorena and John Bobbitt / Patricia J. Priest, Cindy Jenefsky, and Jill D. Swenson -- Women who kill and the made-for-tv movie: the Betty Broderick story / Stephanie Savage -- Victimless crimes and crimeless victims: Lindy Chamberlain and Fairlie Arrow / Helen Yeates -- Re-membering John Bobbitt: castration anxiety, male hysteria, and the phallus / Laura Grindstaff and Martha McCaughey